2004
DOI: 10.1111/j.1365-294x.2004.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of microarray‐based diagnostics of voles and shrews for use in biodiversity monitoring studies, and evaluation of mitochondrial cytochrome oxidase I vs. cytochrome b as genetic markers

Abstract: Molecular methods are widely used for species identification of mammals. In particular, the mitochondrial cytochrome b gene sequence has proven helpful for this purpose. Microarray technology can now open up new perspectives for biodiversity monitoring. With microarrays, many thousands of genetically based characteristics can be tested on one microscopic glass slide called a 'chip'. A 'Mammalia-Chip', for example, could include redundant diagnostic markers to unambiguously identify all European mammal species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 31 publications
(21 reference statements)
4
61
0
Order By: Relevance
“…Altogether, 50 new haplotypes were found in our material from Europe and Asia, generating a total dataset of 70 different water vole cytb haplotypes (Pfunder et al 2004, Centeno-Cuadros and Godoy 2010, Schlegel et al 2012a. Within the 1117-bp long sequences considered here, 106 polymorphic sites were found with a total of 140 mutations, 105 of which were parsimony informative.…”
Section: Molecular Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, 50 new haplotypes were found in our material from Europe and Asia, generating a total dataset of 70 different water vole cytb haplotypes (Pfunder et al 2004, Centeno-Cuadros and Godoy 2010, Schlegel et al 2012a. Within the 1117-bp long sequences considered here, 106 polymorphic sites were found with a total of 140 mutations, 105 of which were parsimony informative.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Included in the study were individuals sequenced for cytb but also museum vouchers of unknown genetic makeup from the same site as the genotyped material. Swiss and German sequences were downloaded from GenBank and their morphotype was not reported (Pfunder et al 2004, Schlegel et al 2012b. Swiss samples were from the range of a subspecies scherman (Meylan and Saucy 1995) and were assigned on this ground to the fossorial morphotype.…”
Section: Morphotypesmentioning
confidence: 99%
“…Phylogenetic effects were controlled using a subset of a phylogenetic tree (Gó mez Montoto et al 2011) reconstructed based on several mitochondrial, nuclear and ribosomal genes (Martin et al 2000, Lundrigan et al 2002, Jaarola et al 2004, Pfunder et al 2004, Suzuki et al 2004, Robovsky et al 2008, Tougard et al 2008, Bannikova et al 2010.…”
Section: Statistical and Phylogenetic Analysesmentioning
confidence: 99%
“…Hebert and Gregory (2005) concluded that though DNA barcoding does not assure complete taxonomic resolution using a single gene region, in many cases when it fails the results can still be resolved fully with additional genetic or other data. Other genes, such as 16S rDNA (Vences et al 2004;Steinke et al 2005;Kappner and Bieler 2006;Aliabadian et al 2009) and Cyt b (Bradley and Baker 2001;Pfunder et al 2004;DeSalle et al 2005;Hajibabaei et al 2007), have been also advocated as standard or as complementary DNA barcoding markers.…”
Section: Introductionmentioning
confidence: 99%